Cambridge Neighbors (from Literary Friends and Acquaintance) - Howells, William Dean, 1837-1920 (Salt Lake City, UT : Project Gutenberg, 2004)
"Cambridge Neighbors (from Literary Friends and Acquaintance)" by William Dean Howells is a reflective memoir written during the late 19th century. This literary work provides an intimate glimpse into the author's life and the rich intellectual environment of Cambridge, Massachusetts, where he interacted with various influential literary figures of his time. Howells captures the essence of friendships and social connections within the literary community, focusing on notable acquaintances and their contributions to literature and culture. In "Cambridge Neighbors," Howells recounts his experiences with remarkable individuals, such as Professor Francis J. Child and poet Hjalmar Hjorth Boyesen, as he reflects on both their personalities and their shared passion for literature. The narrative intertwines biographical sketches with personal anecdotes, revealing the warmth and camaraderie of the literary life in Cambridge. Through engaging stories and poignant observations, Howells illustrates the profound impact of these friendships on his own literary aspirations and the collective creative spirit of the time. The memoir serves as both a tribute to the friendships formed and a commentary on the vibrant literary culture that flourished in Cambridge during that era. (This is an automatically generated summary.)
Release date is 2004-10-22
Produced by David Widger
Keywords: American literature -- 19th century -- History and criticism; Authors, American -- 19th century -- Biography; Howells, William Dean, 1837-1920 -- Friends and associates